Concise enantioselective synthesis of marine macrolide-stagonolide E via organocatalysis - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A short and efficient enantioselective synthesis of marine macrolide stagonolide E in high enantiomeric purity (98% ee and 8.5% overall yield) starting from commercially available raw materials has been achieved. The strategy involves proline catalyzed sequential alpha-aminooxylation and Horner-Wadsworth-Emmons olefination, highly stereoselective Ando's cis-olefination, and modified Yamaguchi macrolactonization as the key reaction steps. (C) 2015 Elsevier Ltd. All rights reserved.

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

Concise enantioselective synthesis of (R)-selegiline, (S)-benzphetamine and formal synthesis of (R)-sitagliptin via electrophilic azidation of chiral imide enolates - Dey, Soumen; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
A concise and high yielding enantioselective synthesis of (R)-selegiline, an anti-Parkinson's drug, (S)-benzphetamine, an anti-obesity agent, and (S)-sitagliptin, an anti-diabetic drug has been described starting from commercially available starting materials employing Evans' electrophilic azidation of chiral imide enolates as a key chiral inducing step, which proceeds in a highly diastereoselective manner (>99%). (C) 2014 Elsevier Ltd. All rights reserved.

Rh-catalyzed synthesis of coumarin derivatives from phenolic acetates and acrylates via C-H bond activation - Gadakh, Sunita K.; Dey, Soumen; Sudalai, Arumugarn (Journal of Organic Chemistry, 2015)
An efficient annulation strategy involving the reaction of phenolic acetates with acrylates in the presence of [Rh-2(OAc)(4)] as catalyst and formic acid as reducing agent, leading to the high yield synthesis of coumarin derivatives, has been developed. The addition of NaOAc as a base increased the yield of the products. The reaction is quite Successful for both electron rich as well as electron deficient phenolic acetates, affording coumarins with excellent regioselectivity, and proceeds via, C-H bond activation proven by deuterium incorporation studies.

Titanium superoxide - a stable recyclable heterogeneous catalyst for oxidative esterification of aldehydes with alkylarenes or alcohols using TBHP as an oxidant - Dey, Soumen; Gadakh, Sunita K.; Sudalai, A. (Organic & Biomolecular Chemistry, 2015)
Titanium superoxide efficiently catalysed the oxidative esterification of aldehydes with alkylarenes or alcohols, under truly heterogeneous conditions, to afford the corresponding benzyl and alkyl esters in excellent yields. Mechanistic studies have established that this ``one pot'' direct oxidative esterification process proceeds through a radical pathway, proven by a FTIR spectral study of a titanium superoxide-aldehyde complex as well as spin trapping experiments with TEMPO. The intramolecular version of this protocol has been successfully demonstrated in the concise synthesis of 3-butylphthalide, an anti-convulsant drug.

Pd-catalyzed reductive cleavage of N-N bond in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates with PMHS: application to a formal enantioselective synthesis of (R)-sitagliptin - Dey, Soumen; Gadakh, Sunita K.; Ahuja, Brij Bhushan; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
An environmentally benign approach involving Pd-catalyzed reductive N-N bond cleavage in dibenzyl-1-alkylhydrazine-1,2-dicarboxylates leading to the synthesis of N-(tert-butoxy)carbamates under very mild conditions has been described. PMHS serves as an inexpensive source of hydride in MeOH/deionized H2O medium. This protocol has been successfully applied in the formal synthesis of (R)-sitagliptin, an anti-diabetic drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: anti-Diabetic; Environmentally benign; Hydrazine; PMHS; Reductive cleavage

Rhodium-catalyzed ortho C-H bond activation of arylamines for the synthesis of quinoline carboxylates - Gadakh, Sunita K.; Dey, Soumen; Sudalai, A. (Organic & Biomolecular Chemistry, 2016)
The rhodium catalyzed annulation of anilines with alkynic esters allowing for the high-yield synthesis of quinoline carboxylates with excellent regioselectivity is described. This unprecedented reaction employs either formic acid as the C1 source and reductant or copper(II) as the oxidant and is proposed to proceed via rhodacycle of in situ generated amide and enamine ester followed by ortho C-H activation of arylamines with rhodium as the catalyst.

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis